SOCIALIZATION OF THE DANGER OF DRUGS TO IMPROVE COLLAGE STUDENT'S AWARENESS - Hartono, Wira Jaya; Fachrurozzie, Ryone (Jurnal ABDIMAS STMIK Dharmapala, 2021)
Drugs are not a dangerous thing if they are used by the experts in medication, but in this case drugs such as crystal meth is consumed by colleagues or university students freely will impact their emotionally and physically. In result it will impact their future to become worse and worse. STMIK Dhamarpala Riau is a college located in central Pekanbaru city. It has freedom of interaction in all aspects, moreover the majority of students are workers. So they become a fresh bait by drug distributors. To prevent that happen and improve their awareness, this is important to give socialization about the danger of drugs in order to avoid bad things occur and they will not trapped in drugs situation. This program is also supported by the National Anti Narcotics Agency of Indonesia. The writer as anti narcotics activators socialize about the definition of drugs, how to recognize drug users, and how to make an anticipation of drug users at the level of family, friends and society. Key Words: Danger of drugs, university student